ANALISIS INTEGRASI MULTIMEDIA DENGAN PENDEKATAN KEMAMPUAN SOSIOLINGUISTIK DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Suruambo, Juharmin; Firman Alamsyah Mansyur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine in depth the role of multimedia integration in improving the sociolinguistic abilities of elementary school students in Indonesian language learning, adopting a mixed-method approach. This study integrates a systematic literature review with primary data collection through classroom observation and interviews. A systematic literature search was conducted on the Scopus database, covering publications up to July 31, 2025, using keywords related to multimedia, sociolinguistics, Indonesian language learning, and elementary schools. Of the 2,666 studies identified, 32 studies met the inclusion criteria after undergoing a rigorous selection process, including a review of the full text. The literature findings show that educational videos and educational games significantly improve students' understanding of formal/informal language use and the social context of language. To enrich the literature findings, this study was followed up with primary data collection through case studies in several elementary schools. Classroom observations were conducted to directly observe the use of multimedia in Indonesian language learning and student interactions related to sociolinguistic aspects. Semi-structured interviews with teachers were also conducted to explore their understanding of the effectiveness of multimedia, implementation challenges, and its impact on sociolinguistic abilities. Primary data will be analyzed using thematic analysis and integrated with literature findings. The combined results show that multimedia, particularly educational videos and games, are effective tools for fostering the sociolinguistic abilities of elementary school students. These findings underscore the importance of planned and relevant integration of multimedia into the Indonesian socio-cultural context. This study identifies challenges in implementing technology in elementary schools, but also highlights significant opportunities to improve the quality of language learning. The implications of this study provide input for educators, curriculum developers, and policymakers to optimize the use of multimedia for the development of students' sociolinguistic competencies.